Analisis Kualitatif Pengaruh Tata Kelola TI Terhadap Transformasi Digital dan Kinerja: Studi Kasus Asuransi A - Uli Artha; Rahmat Mulyana; Luthfi Ramadani (STMIK Budi Darma, 2022)
The emergence of digital technology, innovation competition and government regulations Making BUMN 4.0 disrupt incumbent organizations must carry out digital transformation (DT). It turns out that many of TD's efforts fail to live up to expectations due to poor governance. Previous studies have proven the role of IT governance (ITG). Unfortunately, there are still few studies exploring the mechanism of hybrid ITG that affects DT and organizational performance (OP). Therefore, we propose a research question about how the 46 ITG mechanisms affect DT and OP in the Indonesian insurance industry. Insurance A was chosen because there is a strategic direction for TD acceleration as the basis for digitization. Case study method with qualitative data collection through semi-structured interviews and thematic analysis. This study resulted in 4 themes, 19 sub-themes, and 60 codes and succeeded in demonstrating the mechanism of hybrid ITG that affects DT and the dimensions of DT that affect the achievement of knockout targets through the perspective of BSC in the insurance industry. This research is expected to be a reference for further research as well as an implementation reference to oversee the journey of DT, especially in the insurance industry